Role of the Water–Rock System in the Formation of the Composition of Radon Water of the Tulinskoe Field (Novosibirsk); Russian Geology and Geophysics; Vol. 65, № 12 - Novikov D. A. Dmitry Anatoljevich; Pyryaev A. N. Aleksandr Nikolaevich; Sukhorukov V. P. Vasily Petrovich; Maksimova A. A. Anastasiya Alekseevna; Derkachev A. S. Anton Sergeevich; Sukhorukova A. F. Anna Fedorovna; Dultsev F. F. Fedor Fedorovich; Chernykh A. V. Anatoly Vitaljevich; Khvaschevskaya A. A. Albina Anatolievna; Medeshova N. A. (2024, 2024)
We present the first results of comprehensive isotope-geochemical studies of mineral radon waters of the Tulinskoe field (Novosibirsk), aimed at identifying their stages of interaction with the host rocks. By geochemical coefficients Ca/Na, Ca/Mg, Ca/Si, Mg/Si, Na/Si, Si/Na, rNa/rCl, and SO4/Cl, the studied waters are assigned to fracture–vein waters of granitoids. The indices of carbonate mineral saturation of the radon waters show their oversaturation with aragonite, calcite, and dolomite. The waters are also saturated with diaspore, ferrohydrite, gibbsite, and kaolinite, which leads to the deposition of these minerals as secondary phases. In the thermodynamic diagrams, the points of the activities of the radon water components are localized mainly in the stability fields of clay minerals (kaolinite and Na-, Ca-, and Mg-montmorillonites), layered silicates (talc), and zeolites (laumontite). A few points fall in the stability field of silicates (Mg-chlorite). The studied waters of the Tulinskoe field are neutral fresh, with Si = 6.41–9.02 mg/dm3. According to the results of thermodynamic calculations, the radon waters of the Tulinskoe field are in equilibrium with carbonate minerals and hydromicas. Following the classification by S.L. Shvartsev, they are assigned to the Si-Na geochemical type